A prototipagem enquanto um meio de potencialização da inclusão social e empoderamento de meninas com deficiência - Figueiredo, Natálya Duhart (Universidade do Vale do Rio dos Sinos, 2021)
The invisible barriers imposed by society, which surround and limit people with disabilities are real. In a global context, approximately one billion of individuals are people with disability. Within this amount, a child portion stands out, representing around one hundred and fifty million individuals. The intersection between disability, childhood and the female gender leads to triple discrimination. Social inclusion is defined as a process of improving living conditions and participation in society. It is understood that it is through the expansion of opportunities, accessibility of resources, proportion of spaces for voices to be amplified and respect for essential rights, that inclusion can be effective. From this perspective, empowerment is understood as immersion in a space of awareness and recognition of one's own skills and competences. As a means for empowerment, prototyping was envisaged – from the scope of experimentation and participation, guided by the essence of strategic design – as a reflective project process, questioner and proposer of transformations and worldviews. Thus, it was adopted as a research objective: to understand how prototyping can enhance the empowerment of girls with disabilities. To answer the question, an empirical practice of participatory prototyping was proposed, developed through four cycles of action research. The activities involved the participation of 10 girls with multiple disabilities, aged between 7 and 16 years. The results were divided into five categories - modes: i) experimentation; ii) empowerment; iii) relation; iv) affectation; and v) transformation - and led to 5 main topics of discussion: i) characteristics to be addressed for the design of a participatory prototyping practice; ii) influence of the practice on family dynamics; iii) sensitivity to new ways of being and make; iv) generation of points of view production spaces; and v) affective bonds and the awakening of a sense of belong. Based on the intertwining of the pillars and the reflections revealed, it was considered that the participatory prototyping activity did represent a way of enhancing the girl’s empowerment.
Keywords: Prototipagem; Participação; Inclusão social; Empoderamento de meninas; Design estratégico; Prototyping; Participation; Social inclusion; Girl empowerment; Strategic design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial